1991
DOI: 10.1111/j.1365-2362.1991.tb01817.x
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary hepatic porphyria due to homozygous δ‐aminolevulinic acid dehydratase deficiency: studies in lymphocytes and erythrocytes

Abstract: Activities of delta-aminolevulinic acid (ALA) dehydratase and porphobilinogen (PBG) deaminase, and haem content were determined in EB-virus transformed lymphocytes from two patients with homozygous ALA dehydratase deficiency, and their family members to determine the expression of the specific gene defect in this cell type. ALA dehydratase activity, but not PBG deaminase activity or haem content, was markedly decreased in lymphocyte preparations from both patients with homozygous enzyme deficiency, and moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The patient had ALAD activity less than 3% of normal controls, both in erythrocytes (8) and in lymphocytes (9). Immunochemical studies showed that the proband's cells contained 20% positive crossreactive immunological material (CRIM) (25), suggesting the existence of a structurally altered enzyme(s).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The patient had ALAD activity less than 3% of normal controls, both in erythrocytes (8) and in lymphocytes (9). Immunochemical studies showed that the proband's cells contained 20% positive crossreactive immunological material (CRIM) (25), suggesting the existence of a structurally altered enzyme(s).…”
Section: Resultsmentioning
confidence: 91%
“…Isolation oflymphocytes, transformation ofcells with EBV, and cultivation of lymphoblastoid cells were carried out, as described previously (9). Synthesis ofALAD cDNA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation of lymphocytes and transformation with Epstein-Barr virus were carried out as described previously (15).…”
mentioning
confidence: 99%